2009
DOI: 10.1299/jmmp.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Composite Material Using Coal Ash and Clay

Abstract: Coal ash is industry waste exhausted lots of amount by electric power plant. The particle sizes of coal ash, especially coal fly ash are very fine, and the chemical component are extremely resemble with Okinawa-Kucha clay. From the point of view that clay is composed of particles of micro meter size in diameter, we should try the application for fabrication of composite material using coal fly ash and clay. The comparison of the mechanical properties of composite material using coal fly ash and clay were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…RFAP chemical composition, established using energy dispersive X-ray fluorescence analysis (Shimadzu Corporation, EDX-8000), has been listed in Table 1, and included CaO, derived from waste cement, limestone crushed sand and sea sand, a SiO 2 and Al 2 O 3 ceramic materials. It was noted that, while the RFAP chemical components was similar to that of clay and fly ash, 38 there was a comparatively greater proportion of CaO.…”
Section: Pe and Rfap Preparationmentioning
confidence: 99%
“…RFAP chemical composition, established using energy dispersive X-ray fluorescence analysis (Shimadzu Corporation, EDX-8000), has been listed in Table 1, and included CaO, derived from waste cement, limestone crushed sand and sea sand, a SiO 2 and Al 2 O 3 ceramic materials. It was noted that, while the RFAP chemical components was similar to that of clay and fly ash, 38 there was a comparatively greater proportion of CaO.…”
Section: Pe and Rfap Preparationmentioning
confidence: 99%
“…Similarly, municipal solid waste ash [21,22], blast furnace slag [23][24][25][26], sewage sludge [27,28], and bagasse ash [29][30][31] have been suggested as raw material for ceramic processing. Furthermore, it has been suggested that materials with superior mechanical strength can be developed using the spark plasma sintering (SPS) method with industrial waste as a ceramic raw material [31][32][33][34][35]. The SPS method, which sinters raw material powders within a graphite mould under compression pressure, lowers the sintering temperature and produces materials with superior mechanical properties as compared to hot pressing [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the liquid phase is evident in the three microstructures, but at least present in the sample PC20%P3 which microstructure is less homogenous. According to Fucumoto and Kanda (2009) the sintering process of fl y ash is performed by solid state sintering in the frame of the particles, while the sintering process of compos- ite material including clay is carried out by liquid and solid phase sintering due to lower melting point of clay. Therefore the surfaces around fl y ash particles are surrounded by the melted clay which is solidifi ed as binder around fl y ash particles.…”
Section: Resultsmentioning
confidence: 99%